Impact of oil composition on microwave heating behavior of heavy oils - Zhang, Yang; Adam, Mohamed; Hart, Abarasi; Wood, Joseph; Rigby, Sean P.; Robinson, John P. (American Chemical Society, 2018)
Electromagnetic heating techniques have recently received significant attention as alternatives to conventional heating methods for thermal processing of viscous and heavy oils. One of the benefits of electromagnetic heating is that the electromagnetic field can penetrate the viscous oil and the rock matrix, allowing heating to take place a significant distance away from the electromagnetic source. Opportunities exist for electromagnetic heating in overcoming the heat-transfer limitations within viscous oils, and potentially as a down-hole or in-situ heating technique to raise the temperature within a reservoir. The fundamental interaction of electromagnetic energy with viscous and heavy oils and their constituent components is poorly-understood, and this study enhances the understanding of these interactions at microwave frequencies by establishing the effect of temperature on the dielectric properties of heavy oil and its SARA fractions. The dielectric properties of two heavy oils were studied at temperatures up to 300 °C and frequencies from 900 MHz to 3.0 GHz. The loss factor of both oils was found to increase significantly with temperature, which was linked to a corresponding reduction in viscosity. It is shown for the first time, contrary to previous assertions in the literature, that aromatics and resins are the main contributors towards dielectric loss in heavy oils, whereas saturates and asphaltenes were found to have a negligible influence on the loss factor of the oil. Thus, it will be seen that, at higher temperatures or where there is a high abundance of aromatics and resins, the oils are more susceptible to being heated directly with microwaves, opening up new opportunities for microwave processing of oils in refinery and field settings without a need for microwave-absorbing additives.